FIVE METHODS MENTORING ISLAMIC RELIGION IN DEVELOPING STUDENTS' DIVERSITY ATTITUDES IN HIGH SCHOOLS - Merri Yelliza; Muhammad Yahya; M. Yakub Iskandar; Wahyuni Mulia Helmi (STKIP Pesisir Selatan, 2023)
Morals in Islam occupy an important position and have a vital function in guiding the lives of the people of a nation. Therefore, various efforts are made through the educational process to create people with noble character, including through learning with a model of fostering religious attitudes in the form of mentoring. This research aims to determine the methods used in Islamic religious mentoring activities in developing students' religious attitudes in high schools. This research uses a qualitative method with a case study approach. Data sources were taken through interviews with informants. The main (primary) data sources are mentor teachers and students who directly participate in mentoring activities. Meanwhile, secondary data was taken from school principals, teachers and parents. Researchers used three techniques in collecting data, namely through observation, interviews and documentation studies. The data collected was then processed by reduction, data display, data verification, drawing conclusions and analyzed qualitatively. Research findings found five methods of Islamic religious mentoring in fostering students' religious attitudes in high school. The five methods are; i) lecture method, ii) group discussion method, iii) case study method, iv) assignment method and v) group game method. These findings can be used as a reference for schools and teachers in determining methods for Islamic religious mentoring in schools